2005
DOI: 10.1111/j.1540-8183.2005.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Remodeling and Systolic Deterioration in Acute Myocardial Infarction: Findings from the Stent‐PAMI Study

Abstract: LVSD occurs in a minority of patients despite successful mechanical reperfusion and occurred independent of procedural, angiographic variables, target vessel revascularization, reinfarction, and combined MACE. Infarct size (determined by peak CPK) and high baseline ejection fraction predicted development of LVSD at 6 months. LVSD in this population likely occurred by negative left ventricular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…10 Similarly, in our study, classical biological parameters of infarct size as troponin or CK or electrocardiographic criteria of microvascular reperfusion as ST resolution were not different between patients with and without LV remodeling.…”
Section: Discussionmentioning
confidence: 76%
“…10 Similarly, in our study, classical biological parameters of infarct size as troponin or CK or electrocardiographic criteria of microvascular reperfusion as ST resolution were not different between patients with and without LV remodeling.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, the prognostic significance of LV ESV after AMI has been established using analysis of LV angiograms 7. In addition, recent large‐scale intervention studies have also relied on quantitative analysis of LV angiograms to document the effects of PCI on convalescent LV function 11,12,22. Using paired LV angiograms from individual patients for serial analysis reduces the impact of geometric assumptions inherent in any two‐dimensional imaging method (like LV angiography) used for quantification of the three‐dimensional geometry of an infarcted heart.…”
Section: Discussionmentioning
confidence: 99%
“…Use of interventional therapeutics (percutaneous coronary intervention, PCI) to recanalise the occluded infarct-related artery, thereby improving or normalising coronary blood flow, may delay the ventricular remodelling, but cannot preventing or even reverse this process, which represents a major cause of late infarct-related chronic heart failure 2 3. On the basis of pluripotential cells in the bone marrow capable of further differentiating into endothelium, smooth muscle cells and cardiac myocytes,4 5 recent experimental and clinical studies have shown that intracoronary transfer of unselected bone marrow mononuclear cells (BMC) in patients with acute MI considerably increases heart function by apparently repairing damaged cells beyond the recovery which occurs with PCI 610.…”
mentioning
confidence: 99%